The effect of maternal migraine headache on their children's quality of life - ERDOĞDU, AYŞE BURCU (SPRINGER HEIDELBERG, 2017)
Migraine is an episodic disease characterized by a throbbing and generally unilateral headache, often accompanied by nausea, vomiting and light and sound sensitivity. Migraine is known to affect one's quality of life; not only the person with migraine but also his/her family and social environment are affected by this condition. Our study aimed to evaluate the effects of maternal migraine on children's quality of life. The patient group comprised 70 mothers with migraine diagnoses and their 111 healthy children, while 50 healthy mothers and their 86 children were included in this study as the control group. The Visual Analog Scale (VAS), Migraine Disability Assessment Scale, Beck Depression Index (BDI) and Beck Anxiety Index (BAI) were used for evaluation of mothers; 3 to 7-year old KINDL and 7- to 17-year-old KINDL-R Quality of Life Scales were used to evaluate the quality of life of children. The SPSS 21.0 program was used for statistical analysis and p < 0.05 was assumed to be statistically significant. The mean age of the migraine group was 37.09 +/- 6.94 years, and the mean age of the control group was 38.2 +/- 4.5. Symptoms of depression and anxiety were more frequently found in subjects with migraine (p < 0.05). In comparison with the control group: 3 to 7-year old KINDL total scores, self-esteem and school subscales, 7- to 17-year-old KINDL total scores, self-esteem and the social relationships subscale scores were lower in migraine group. It was found to be significant that VAS, BDI and BAI scores of the mothers were negatively correlated with the children's quality of life. Our study concluded that the presence of migraine-type headache in mothers worsen the relations in school, self-esteem and quality of life in younger children and social relations, relations in school and quality of life in older children. The maternal age, disease severity, and anxiety and depression symptoms were shown to predict the quality of life in children. Performing preventive interventions by individually assessing bio-psycho-social elements for the treatment of mothers with migraine will preserve other family member's and especially children's quality of life.
Keywords: Migraine; Children; Quality of life; PSYCHOMETRIC PROPERTIES; EPISODIC MIGRAINE; CHRONIC PAIN; POPULATION; DISABILITY; SYMPTOMS; QUESTIONNAIRE; PREVALENCE; DISORDERS; INVENTORY